Eliciting beliefs by paying in chance - Alvaro Sandroni; Eran Shmaya (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2013)
This paper describes a general principle that can be used to elicit honest opinions, even if risk attitudes are unknown.
Keywords: D83; 330; Scoring Rule; Eliciting Beliefs